PENANAMAN NILAI AKHLAK BERBASIS PENDIDIKAN ISLAM SEBAGAI LANDASAN TEORI PENDIDIKAN KARAKTER DI SEKOLAH - M. Shalahuddin; Lala Tansah; Aan Hasanah; Bambang Samsul Arifin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research examines the importance of instilling moral values based on Islamic education as a theoretical foundation for character education in schools. The main objective of this study is to explore the incorporation of Islamic values such as honesty, compassion, humility, and justice into the character education curriculum for shaping students' character. The research method used includes a literature review to gather data on the effectiveness of Islamic-based character education in various educational contexts. The results of the study indicate that this approach not only strengthens individual morality but also promotes religious identity, tolerance, and independence among students in facing global moral challenges. The implications of these findings are that Islamic-based character education is a relevant and effective strategy in preparing future generations who are responsible, have integrity, and are empathetic towards society. Keywords: Instilling Moral Values, Theoretical Foundation of Character Education.